2014
DOI: 10.3389/fncel.2014.00312
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine in the antiepileptic effects of deep brain stimulation

Abstract: Despite the effectiveness of anterior thalamic nucleus (AN) deep brain stimulation (DBS) for the treatment of epilepsy, mechanisms responsible for the antiepileptic effects of this therapy remain elusive. As adenosine modulates neuronal excitability and seizure activity in animal models, we hypothesized that this nucleoside could be one of the substrates involved in the effects of AN DBS. We applied 5 days of stimulation to rats rendered chronically epileptic by pilocarpine injections and recorded epileptiform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…P2Y12 knockout mice exhibited reduced seizure-induced increases in microglial process numbers and worsened kainate-induced seizure behaviours [85]. It has been suggested that the antiepileptic effects of deep brain stimulation may be mediated by adenosine [86]. Experiments support a role for post-transcriptional regulation of the P2X7 receptors and it was suggested that therapeutic targeting of microRNA-22 may prevent inflammation and development of epilepsy [87].…”
Section: Epileptic Seizuresmentioning
confidence: 99%
“…P2Y12 knockout mice exhibited reduced seizure-induced increases in microglial process numbers and worsened kainate-induced seizure behaviours [85]. It has been suggested that the antiepileptic effects of deep brain stimulation may be mediated by adenosine [86]. Experiments support a role for post-transcriptional regulation of the P2X7 receptors and it was suggested that therapeutic targeting of microRNA-22 may prevent inflammation and development of epilepsy [87].…”
Section: Epileptic Seizuresmentioning
confidence: 99%
“…Previous studies using the pilocarpine model have shown that anterior thalamic nucleus (ANT) DBS reduced the latency to seizures and SE onset (5,(12)(13)(14)(15). In chronic pilocarpine epileptic rats, ANT stimulation reduced hippocampal excitability and seizure rate (12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the local electrical effects of DBS, researchers found that DBS could also induce neurochemical changes locally and through the stimulated network. For instance, DBS of the anterior thalamus for the treatment of epilepsy in a rodent model induces the release of hippocampal adenosine [39]. Moreover, DBS has shown to induce plastic changes with regard to synaptic plasticity and neurogenesis.…”
Section: Mechanisms Of Dbsmentioning
confidence: 99%